Cognitive Interview Associated With Memory Box: Contributions to Narrative Research With the Use of Testimonies (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
This article is the result of a research narrative, whose objective was to produce and present understandings about the creation and use of a device that associates cognitive interview (CI) and memory box to obtain testimonies. Two teachers from the Science Club of the Federal University of Pará in the Legal Amazon participated. The application of this device originates or a free testimony and a dialogue, which were transcribed and constituted the corpus of the research. For the analysis of the material, we adopted the software IRAMUTEQ associated with Discursive Textual Analysis (DTA). The corpus was processed, and, with DTA criteria, two categories emerged, through which it was possible to inventory the information contained in the testimonies and infer units of meanings that justify them. We conclude that the memory activator device considerably increases the volume and quality of information obtained as testimonies, contributing in a relevant way to narrative research.